THE TMPRSS2:ERG REARRANGEMENT, ERG EXPRESSION, AND PROSTATE CANCER OUTCOMES: A COHORT STUDY AND META-ANALYSIS - Pettersson, Andreas (2012)
BACKGROUND: Whether the genomic rearrangement TMPRSS2:ERG has prognostic value in prostate cancer is unclear. METHODS: Among men with prostate cancer in the prospective Physicians’ Health and Health Professionals Follow-Up Studies, we identified rearrangement status by immunohistochemical assessment of ERG protein expression. We used Cox models to examine associations of ERG overexpression with biochemical recurrence and lethal disease (distant metastases or cancer-specific mortality). In a meta-analysis including 47 additional studies, we used random effects models to estimate associations between rearrangement status and outcomes. RESULTS: The cohort consisted of 1,180 men treated with radical prostatectomy between 1983 and 2005. During a median follow-up of 12.6 years, 266 men experienced recurrence, and 85 men developed lethal disease. We found no significant association between ERG overexpression and biochemical recurrence (HR: 0.99; 95% CI: 0.78-1.26) or lethal disease (HR: 0.93; 95% CI: 0.61-1.43). The meta-analysis of prostatectomy series included 5,074 men followed for biochemical recurrence (1,623 events), and 2,049 men followed for lethal disease (131 events). TMPRSS2:ERG was associated with stage at diagnosis (RR(≥T3 vs. T2): 1.23; 95% CI: 1.16-1.30) but not with biochemical recurrence (RR: 1.00; 95% CI: 0.86-1.17) or lethal disease (RR: 0.99; 95% CI: 0.47-2.09). CONCLUSIONS: These results suggest that TMPRSS2:ERG, or ERG overexpression, is associated with tumor stage but does not strongly predict recurrence or mortality among men treated with radical prostatectomy. IMPACT: This is the largest prospective cohort study to examine associations of ERG overexpression and lethal prostate cancer among men treated with radical prostatectomy.